Boron nitride nanosheets can induce water channels across lipid bilayers leading to lysosomal permeabilization - Lucherelli, Matteo Andrea (2021)
While the interaction between 2D materials and cells is of key importance to the development of nanomedicines and safe applications of nanotechnology, still little is known about the biological interactions of many emerging 2D materials. Here, an investigation of how hexagonal boron nitride (hBN) interacts with the cell membrane is carried out by combining molecular dynamics (MD), liquid-phase exfoliation, and in vitro imaging methods. MD simulations reveal that a sharp hBN wedge can penetrate a lipid bilayer and form a cross-membrane water channel along its exposed polar edges, while a round hBN sheet does not exhibit this behavior. It is hypothesized that such water channels can facilitate cross-membrane transport, with important consequences including lysosomal membrane permeabilization, an emerging mechanism of cellular toxicity that involves the release of cathepsin B and generation of radical oxygen species leading to cell apoptosis. To test this hypothesis, two types of hBN nanosheets, one with a rhomboidal, cornered morphology and one with a round morphology, are prepared, and human lung epithelial cells are exposed to both materials. The cornered hBN with lateral polar edges results in a dose-dependent cytotoxic effect, whereas round hBN does not cause significant toxicity, thus confirming our premise.